Audit partner narcissism and audit reports readability : evidence from lead and review audit partners - Rajabalizadeh, Javad; Schadewitz, Hannu (Emerald, 2025)
Purpose – This study aims to investigate the impact of audit partners’ narcissism on the readability of audit
reports for companies listed on the Tehran Stock Exchange (TSE). It examines the effects of narcissism among both lead and review audit partners on the clarity of audit reports, considering the regulatory requirements and auditing practices within the Iranian financial reporting context.
Design/methodology/approach – This paper analyzed 2,691 firm-year observations from TSE-listed
companies spanning 2011–2023, using ordinary least squares regression. Readability of audit reports was
assessed using the FOG index, with the size of partners’ signatures serving as a proxy for narcissism.
Findings – The findings indicate a significant negative relationship between increased narcissism and audit
report readability; higher levels of narcissism correspond with elevated FOG index scores. Narcissism in lead partners notably diminishes readability more than that of review partners. This pattern holds across various robustness checks, including alternative readability metrics, variations in auditor engagement complexity, auditor specialization, subsets of qualified audit reports and considerations for endogeneity. Audit reports for economically significant clients tend to be clearer, suggesting a preference for reputation management over yielding to client pressure. Although no direct link was established between partners’ quality and readability, a positive relationship exists between audit firm rank and partners’ narcissism. Furthermore, interactions between auditor and CEO narcissism increase report complexity, especially in contentious negotiation scenarios. Despite regulatory advancements such as International Auditing Standard 701, its moderating effects were
found to be inconsequential, highlighting the persistent influence of narcissismon audit report outcomes.
Originality/value – This research expands the understanding of how auditor personality traits, particularly
narcissism, affect audit outcomes. By exploring the influence of narcissism on report readability within the
Iranian context, this study fills a notable gap in the literature on emerging markets and non-Western reporting environments, providing valuable insights into global audit practices.